Conservation of Cultural Heritage Architecture and Development of Tourism in Denpasar, Bali - Runa, I Wayan; Warnata, I Nyoman; Anasta Putri, Ni Putu Ratih Pradnyaswari (Universitas Pendidikan Indonesia, 2019)
This research aims to examine the role of conservation of cultural heritage architecture in the development of tourism in Denpasar and to describe the concept that shapes the downtown Denpasar (zone Z). Following the characteristics of the object of study (research questions), this research uses phenomenology as the paradigm. The qualitative method (phenomenology) is an inclusive and flexible method, which is always developing. This method helps to gain an understanding of meaning, develop theories, and describes complex realities. This research was conducted with the help of human instruments (the researchers), notebooks, voice recorders, and research assistants. Additionally, this research emphasizes qualitative techniques, in which researchers or human factors have an important role. Primary data consist of words and actions, while secondary data include documents, photos, and statistics. Results show that the cultural life of Denpasar citizen has a significant effect on the development of tourism in Denpasar, Bali. It is evident in the structure, functions, and meaning of downtown Denpasar Heritage City, especially in managing the area, planning, and building layout. The downtown Denpasar has a unique pattern calledÂ Pempatan Agung. In the context of tourism, the development of Denpasar should focus on creativity and culture. The responsibility of managing the area should be shouldered by the community, cultural experts, universities, NGOs, private companies, and the government. Also, there needs to be a continuous evaluation of the results of management.Â Keywords:Â Pempatan Agung, culture, creativity.